TRAFFIC POLICE OPTIMIZATION IN ENFORCING TRAFFIC VIOLATIONS IN THE JURISDICTION OF BOGOR CITY POLICE - Teguh Permana , Muhammad; Nurwati; Ilyanawati, R. Yuniar Anisa (DE’RECHTSSTAAT, 2025)
Many motorcyclists are aware of the safety riding program that is often published by various parties, especially the traffic police. However, it seems that the introduction and campaign of the safety riding concept alone is not enough to explain to motor vehicle drivers about road safety. Minor to major violations are still often found. Research methods are needed to collect a number of materials used to answer the legal analysis. Starting from the problem, the research method used is the normative legal research method, namely the law is conceptualized as norms, rules, principles or dogmas. The Traffic Police (Polantas) is responsible for traffic regulations on the highway, this unit assists other elements in the police to handle violations of the law on the highway. For this reason, there are four steps that are the main characteristics of the Polantas task, namely traffic law enforcement (both preventive and repressive), public education about traffic, traffic engineering, and registration and identification of drivers and motor vehicles. In addition, Polantas serves the community in managing STNK, SIM, and helping with traffic accidents.